سياسة إنجلتراإتجاه السودان 1924م-1953م - بركات سلمى (جامعة محمد بوضياف بالمسيلة, 2025)
تركزهذه الدراسة على السياسة الاستعمارية البريطانية في السودان مابين عامي 1924م و1953م ,مركزة على السياسة الإدارية و الإجتماعية لهذه المرحلة ,وتناولت هذه الدراسة أسس نظام الحكم الثنائي المصري الإنجليزي الذي أقر في اتفاقية 1899م هذا النظام المركزي يعتمد على الهيمنة المباشرة , إلا أنه بعد 1924م انتهجت بريطانيا أسلوبا إستعماريا عبر دعم القيادات المحلية و تطبيق سياسة المناظق المقفولة ,للحد من تنامي الوعي القومي إلا أنه وبالرغم من ذلك فقد أسهمت هذه السياسات في تنشيط الحراك السياسي و بروز الحركات الوطنية و التنظيمات الطلابية والنقابية ,كما تظهر دور المحوري لمؤتمر جوبا 1947م و الجمعية التشريعية 1948م في بلورة العمل السياسي المنظم ليتوج هذا بتوقيع اتفاقية الحكم الذاتي و تمهيد الطريق للإستقلال الكامل عام 1956م ,اعتمد على المنهج التحليلي التاريخي لفهم التفاعل بين السياسة الاستعمارية و مسارات المقاومة الوطنية في السودان This study focuses on British colonial policy in Sudan between 1924 and 1953, emphasizing the administrative,, and social policy of that period. It examined the foundations of the Anglo-Egyptian Condominium which was approved in the 1899 Agreement, which introduced a central system adopts hegemony. However, after 1924, Britain pursued a new colonial approach by supporting local leaders and implementing the Closed Districts Policy to curb the growing sense of national awareness. Despite these efforts, such policies to limit ,the rise of political activism and the emergence of national movements, student unions, and labor organizations. The study also shows the important role of the Juba Conference in 1947 and the establishment of the Legislative Assembly in 1948 in formulated organized political action. These developments culminated in the signing of the Self-Government Agreement, paving the way for Sudan’s full independence in 1956. The study adopts a historical-analytical method approach to understand the interaction between colonial policy and the paths of national resistance in Sudan